SINDROM HIPERSENSITIVITAS DAPSON PADA PASIEN MORBUS HANSEN MULTI-BASILER: LAPORAN KASUS - Bandjar, Fitri Kadarsih (Fakultas Kedokteran Universitas Pattimura, 2024)
Dapsone syndrome is a syndrome that occurs after dapsone therapy within a period of 48 hours to 6 months after dapsone use and does not depend on the drug dose. The clinical manifestations can resemble other drug allergies and have a fatal risk if not treated properly.The classic triad of dapsone syndrome consists of fever, internal organ involvement and skin eruption/exfoliative dermatitis. The diagnosis of dapsone hypersensitivity syndrome is made if a hypersensitivity reaction occurs after dapsone therapy for 2-8 weeks followed by two of the following symptoms: fever, skin eruption, lymphadenopathy, and impaired liver function. Treatment of dapsone hypersensitivity syndrome is to immediately stop the dapsone drug and administer adequate corticosteroids. We report the case of a 19-year-old male diagnosed with multibacillary leprosy and receiving multidrug therapy-multibacillary (MDT-MB) therapy for the second month. Six weeks after starting therapy, fever, bumps and sores appeared almost all over the body accompanied by yellow eyes. On physical examination, hyperpigmented macules, nodules, ulcers, anemic conjunctiva and icteric sclera were found. Laboratory examination revealed anemia, leukocytosis, and increased liver enzymes. Based on clinical findings and supporting examinations, a diagnosis of dapsone hypersensitivity syndrome was made. After starting dapsone and administering desoxymethasone 5 mg per 24 hours intravenously, then tapered, clinical and laboratory findings showed improvement.